THE RELATIONSHIP BETWEEN CSR AND FINANCIAL DISTRESS: MODERATED BY CORPORATE LIFE CYCLE - Lusmeida, Herlina; Tjendriawan, Bella (Faculty of Economics and Business Universitas Pelita Harapan, 2024)
This research aims to prove empirically the relationship between Corporate Social Responsibility (CSR) performance and Financial Distress. Also to prove empirically how Mature Stage of Corporate Lifecycle is moderating the relationship between CSR performance and Financial Distress. The independent variable (CSR) is divided into 2 categories namely positive and negative. The populations are consumer sectors companies listed on the IDX during the period of 2018-2020. Based on purposive sampling criteria, the total observation for this study is 153 companies. Data were analysed using logistic regression analysis method by using a statistical software namely SPSS version 26. The results showed that positive corporate social responsibility has negative significant relationship with financial distress and mature stage of corporate life cycle is not significantly strengthen the relationship between positive corporate social responsibility and financial distress.